Ecotrophelia Portugal (2017-2020): content analysis of a competition to promote academic entrepreneurship and food innovation - Oliveira, Leandro (2022)
Introduction: The food sector is considered worldwide as one of the main business sectors, being constantly changing and facing multiple challenges. Objectives: This paper aims to describe the finalist teams and products in the competition for the Ecotrophelia Portugal (2017-2020) as sources of innovation for the food sector. Methodology: A content analysis approach was adopted. The analyzed contents were collected through the official website of Ecotrophelia Portugal. Information from the 41 finalist teams in the competition between 2017 and 2020 was analyzed. Results: In general, most of the finalists were female (2017 edition), belonging to the North region (57.4%), followed by the Centro region (27.9%) and Lisbon (13.1%), with the Universidade do Porto (26.2%), Universidade Católica Portuguesa (Porto: 16.4%) and the Instituto Politécnico de Coimbra (13.1%) being the main institutions from which the finalists came. The main categories to which the finalist products belonged were: snacks (34.1%), desserts (17.1%), ready-to-eat meals (12.2%), drinks (9.8%). The characteristics most mentioned in the description of these products were that they are: rich in bioactive compounds (34.2%), gluten / lactose free or low in sugar / fat (19.0%), healthy (11.4%) and vegetarian / vegan (11.4%). Conclusions: This study provides useful information for future competitors to new editions of this competition, as well as a source of inspiration for the development of new food products by entrepreneurs.